Health System Responsiveness for Persons with HIV and Disability in South Western Uganda - Kibet, Emmanuel; Namirimu, Florence; Nakazibwe, Felista; Kyagera, Arnold Zironda; Ayebazibwe, Disan; Omech, Bernard (HIV/AIDS-Research and Palliative Care, 2023)
Background: Inequitable access to Human Immunodeficiency Virus/Acquired Immune Syndrome (HIV/AIDS) Treatment and Care Services (HATCS) for People with Disabilities (PWD) is a hurdle to ending the pandemic by 2030. The aim of this study was to evaluate the Health System’s Responsiveness (HSR) and associated factors for PWD attending HATCS at health facilities in South Western Uganda. Methods: Between February and April 2022, we enrolled a total of 106 people with disabilities for a quantitative study and 14 key informants from selected primary care HIV clinics. The World Health Organization Multi-country study’s disability assessment schedules 2.0 and Health system responsiveness (HSR) questionnaire were adopted to measure the level of disabilities and responsiveness, respectively. The level of HSR was evaluated using descriptive analysis. The association between socio-demographics, level of disabilities and HSR was evaluated through binary and multivariable logistic regression. The qualitative data were collected from 14 key informants using interview guide and analyzed according to thematic areas (deductive approaches). Results: Overall, Health system responsiveness (HSR) was at 47.62% being acceptable to people living with HIV and Disabilities in south western Uganda. Across different domains, the best performance was reported in social consideration (68.57%) and autonomy (67.62%). The least performance was registered in dignity (2.83%), confidentiality (2.91%), prompt Attention (17.35%) and Choices (30.48%). Whereas performance in communications (53.92%) and quality of basic amenities (42.27%) were average. There were no socio-demographics or disability variables that were predictive of HATCS responsiveness. PWDs experienced lack of social support, poor communication, stigma and discrimination during the HATCs services. On the other hand, the health-care providers felt frustrated by their inability to communicate effectively with PWDs and meet their need for social support. Conclusion: HSR was comparatively low, with dignity, confidentiality, prompt attention, and choice ranking worst. To address the universal and legitimate requirements of PWDs in accessing care, urgent initiatives are required to create awareness among all stakeholders.
Keywords: HIV/AIDS; Disability; Health system responsiveness; Uganda